Waterproof sheet for heat-shielding tent membrane structures with excellent weather resistance
Patent Information
- Application Number
- JP2022189977
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-11-29
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2042-11-29
AI Technical Summary
【0013】 本発明により、耐用年数が向上した遮熱テント膜構造物を得ることができる。すなわち耐候性(紫外線劣化軽減)、及び防黴(藻)性に優れることで、きれいなままの外観を長期間維持できる遮熱テント膜構造物の提供が可能となる。具体的に、屋内スポーツ施設、イベントパビリオン、移動サーカス、プラネタリウム、テント倉庫などの長期使用(10~15年)のテント構造物などに最適となり、さらに、建築養生(防音)シート、パーゴラシェード(膜天井)、ファサードシート、昇降式シートシャッター、間仕切りシート、トラック幌、野積防水シート、屋形テントなどの10年未満の用途にも展開可能となる。特に、遮熱テント膜の耐用年数が延長されることによって、廃棄頻度(すなわち張替)が減り、同時に膜材の生産量も減ることで二酸化炭素排出の要因となる石化資源の消費を抑え、持続性の地球環境保全に貢献することができるようになる。
Smart Images

Figure 0007638001000001 
Figure 0007638001000002 
Figure 0007638001000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a tent membrane structure that has heat-shielding properties and can withstand long-term use, i.e., a heat-shielding tent membrane structure with an extended service life, and more specifically, to an architectural structure equipped with a heat-shielding tent membrane whose service life has been extended by preventing discoloration due to sunlight over time, preventing deterioration due to sunlight, and preventing the growth of mold and algae in order to maintain its appearance. [Background technology]
[0002] There are two types of closed-type tent membrane structures: those that are primarily used for entertainment (people), such as indoor sports (tennis, futsal, bouldering, etc.), event halls, pavilions, traveling circus tents, video projection domes, and glamping, and those that are primarily used for storing and stockpiling factory materials and distributing products (goods), such as tent warehouses. All of them use synthetic fiber fabrics such as polyester fiber fabrics as the base material, and tarpaulins or waterproof canvases that are covered with thermoplastic resin layers such as soft polyvinyl chloride resins on both sides. Closed-type tent membrane structures have entrance doors and opening / closing windows, and when these are closed, they form an enclosed space. On the other hand, open-type tent membrane structures are open-ceiling structures that mainly use a roof structure, and specifically, they are sunshade monuments in parks and theme parks, garden terrace roofs installed in the space between buildings, pergola shades, etc. Closed-type tent membrane structures protect people and goods from wind, rain, and sunlight, but have the disadvantage that they are semi-transparent to allow light in, so that the heat from the sun in summer tends to build up inside. On the other hand, while open-type warehouses are well ventilated, they are not suitable for protecting people and goods from the elements. In particular, closed-type tent membrane structures, those used primarily for entertainment (people) are equipped with air conditioning and heating / cooling equipment, but tent warehouses used primarily for logistics (goods) are rarely equipped with such equipment. However, the heat builds up inside tent warehouses in the summer, making them a harsh environment, so for those who manage, store, and retrieve factory materials, measures against heatstroke such as electric fans and spot coolers are essential.
[0003] In order to reduce the heat inside such a tent warehouse, it is effective to make the tent membrane (tarpaulin, waterproof canvas) a reflective color such as white or silver. In particular, it is known that titanium oxide pigments have a high refractive index and therefore a high light scattering power, which results in a high solar reflectance (heat shielding rate). However, the greater the light scattering power, the higher the concealing power becomes, and the light gathering ability of the tent membrane is hindered, so that the inside of the tent warehouse becomes an environment where lighting is required even during the day. In response to this dilemma, the applicant previously proposed a membrane material (Patent Document 1) for a tent (warehouse) that combines a heat shielding effect and light gathering ability, in which the thermoplastic resin coating layer of the membrane contains 0.3 to 30 mass % of amorphous inorganic compound particles (titanium oxide) with a refractive index of 1.8 or more, a particle size distribution of 0.3 to 3.0 μm, and an aspect ratio of 1.0 to 3.0. In this embodiment, a heat shielding rate of 38-65% and daylighting with a light transmittance of 4-45% can be obtained, and the effect of reducing the power consumption of air conditioning in summer and lighting throughout the year can be expected. However, the price of daylighting with a light transmittance of 4-45% is that the tent membrane (thermoplastic resin coating layer) may discolor due to ultraviolet damage caused by light transmission, or the surface may crack, resulting in a risk of shortening the service life of the membrane material. As one of the recent efforts toward the SDGs, a tent membrane material that can be used for a long time is desired. This is because extending the service life of the tent membrane material by several years will lengthen the replacement cycle of the tent membrane material, reducing the consumption of petrochemical resources that are the raw materials for synthetic fiber fabrics and thermoplastic resins used to manufacture the tent membrane material, and will also contribute to society by reducing carbon dioxide emissions.
[0004] Specifically, as a means for improving the service life of tent (warehouse) membrane materials made of soft polyvinyl chloride resin, the applicant has proposed a method of blending an ultraviolet absorbing agent into a soft polyvinyl chloride resin layer (Patent Document 2), a method of providing a coating layer blended with a high molecular weight ultraviolet absorbing agent on the surface of a heat-shielding composite sheet (Patent Document 3), and a light-transmitting heat-shielding membrane material having a photocatalytic outermost layer as an outdoor membrane material that prevents soot-dust stains that reduce the heat-shielding effect for a long period of time and has excellent light-transmitting, heat-shielding and stain-removing properties (Patent Document 4).In addition, the applicant has proposed a mildewproofing agent containing an inorganic mildewproofing substance as the main component, and an aesthetically sustaining laminated membrane material with a photocatalytic outermost layer as a membrane material that can prevent environmental stains such as soot-dust stains and discoloration due to mold for a long period of time (Patent Document 5). All of these have useful effects, but as one of the recent SDGs initiatives, there is a demand for building structures equipped with heat-insulating tent membranes that can be used for the long term, and there is an urgent need to find a technological solution to extend their service life. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2007-055177 A [Patent Document 2] Japanese Patent Application Publication No. 59-41249 [Patent Document 3] JP 2001-225423 A [Patent Document 4] JP 2003-251728 A [Patent Document 5] JP 2003-053905 A Summary of the Invention [Problem to be solved by the invention]
[0006] The problem to be solved by the present invention is to improve the service life of a heat-shielding tent membrane structure, that is, to provide a building structure equipped with a heat-shielding tent membrane that has excellent weather resistance (reduction of ultraviolet degradation) and mold (algae) resistance in order to maintain the appearance and basic performance. In addition, the object of the present invention is to contribute to global environmental conservation by extending the service life of a heat-shielding tent membrane structure, thereby reducing the frequency of disposal (i.e. replacement) and reducing waste. [Means for solving the problem]
[0007] As a result of considering these points and carrying out repeated studies, the heat-shielding tent membrane structure of the present invention, which has excellent weather resistance, Waterproof sheet for A tent membrane structure is a structure in which a waterproof sheet is attached to the outer periphery of the side walls of a frame structure that forms a space and to the canopy. Waterproof sheet for The waterproof sheet is "Surface heat Plastic resin layer / fabric / Backside heat A sewn product is made of a plurality of flexible laminates each having a "plastic resin layer" structure, and at least surface heat The plastic resin layer is made of surface-treated titanium oxide particles having an average primary particle size of 0.4 to 1.2 μm, a keto / enol tautomer, and Antifungal Agent of Contains as an essential ingredient , the surface treatment applied to the surface-treated titanium oxide particles is performed with one or more metal oxides selected from aluminum oxide, zirconium oxide, silicon oxide, and aluminum hydroxide, and the keto / enol tautomer is one or more selected from benzotriazole-based tautomers, triazine-based tautomers, and diphenyl ketone-based tautomers, and further a thin film layer is formed on the surface thermoplastic resin layer, and this thin film layer contains one or more keto / enol tautomers selected from benzotriazole-based tautomers, triazine-based tautomers, and diphenyl ketone-based tautomers, and an N-OR hindered amine; This makes it possible to obtain architectural structures equipped with heat-shielding tent membranes that have excellent weather resistance (reduction of UV degradation) and mold resistance (algae), and it is possible to improve the service life of heat-shielding tent membrane structures. As a result, the frequency of disposal (i.e. replacement) of heat-shielding tent membranes (waterproof sheets) will decrease, and at the same time, the production volume of membrane material will decrease, thereby reducing consumption of petrochemical resources that are a cause of carbon dioxide emissions, and contributing to the conservation of a sustainable global environment. This is the belief that has led to the completion of this invention. *In the following paragraphs, "(surface) thermoplastic resin layer" shall be read as "surface thermoplastic resin layer", "(back) thermoplastic resin layer" shall be read as "back thermoplastic resin layer", and "mold (algae) antifungal agent" shall be read as "mold inhibitor".
[0008] The heat-shielding tent membrane structure of the present invention has excellent weather resistance Waterproof sheet for The keto / enol tautomers are benzotriazole tautomers, triazine tautomers, and diphenylketo tautomers. N seriesIt is preferable that the keto / enol tautomer is one or more selected from the group consisting of enol isomers and keto isomers. This keto / enol tautomer is subjected to repeated mutual conversion between the enol isomer and the keto isomer in nanosecond units by stimulation with sunlight (ultraviolet rays), so that the enol and keto isomers coexist in equilibrium within the thermoplastic resin layer, and the ultraviolet energy received is converted into thermal energy of molecular vibrations in the mutual conversion and released outside the system. This energy attenuation effect reduces damage caused by ultraviolet rays, thereby improving the durability of the heat-shielding tent membrane (waterproof sheet).
[0009] The heat-shielding tent membrane structure of the present invention has excellent weather resistance Waterproof sheet for teeth, The surface thermoplastic resin layer, or the surface thermoplastic resin layer and the back surface thermoplastic resin layer The present invention further comprises zinc oxide or a mixture of titanium oxide and zinc oxide, and the zinc oxide and titanium oxide are formed on the particle surface. Made of one or more metal oxides selected from aluminum oxide, zirconium oxide, and silicon oxide. It is preferable that the coating layer has a primary average particle diameter of 0.3 μm or less. This allows zinc oxide or zinc oxide and titanium oxide particles with a primary average particle diameter of 0.3 μm or less (0.1 μm to 0.3 μm) to enter the gaps between the surface-treated titanium oxide particles with a primary average particle diameter of 0.4 to 1.2 μm contained in the thermoplastic resin layer, and the zinc oxide and titanium oxide particles with this particle diameter can scatter ultraviolet rays that penetrate into the thermoplastic resin layer to block the transmission of ultraviolet rays. In particular, zinc oxide has an excellent UVA (ultraviolet A wave) blocking effect, and titanium oxide has an excellent UVB (ultraviolet B wave) blocking effect, so that the durability of the heat-shielding tent film (waterproof sheet) is improved by using a mixture of titanium oxide and zinc oxide. The zinc oxide and titanium oxide particles used in the present invention are ultraviolet blocking agents that do not deteriorate the thermoplastic resin layer in which the photocatalytic activity is sealed by surface treatment.
[0010] The weather-resistant heat-shielding tent membrane structure of the present invention preferably has a thin film layer formed on the (surface) thermoplastic resin layer, which contains one or more keto / enol tautomers selected from benzotriazole tautomers, triazine tautomers, and diphenyl ketone tautomers, and N-OR hindered amines. This keto / enol tautomer repeats mutual conversion between enol isomers and keto isomers in nanosecond units when stimulated by sunlight (ultraviolet rays), so that the enol and keto isomers coexist in equilibrium in the thin film layer, and the ultraviolet energy received is converted into thermal energy of molecular vibrations in the mutual conversion and released outside the system, thereby reducing damage to the (surface) thermoplastic resin layer caused by ultraviolet rays through the manifestation of an energy attenuation effect. N-OR hindered amine compounds capture peroxide radicals (ROO·) produced by UV damage in the N-OR portion, neutralize them into alcohols and ketones, and release them. They then convert themselves into nitroxy radicals (NO·), capture alkyl radicals (R·) produced by UV damage, and the N-OR hindered amine compound returns to its original state. This cycle is repeated on a nanosecond basis, preventing the chain reaction of bond cleavage within the thin film layer caused by the attack of harmful radicals, and improving the durability of heat-shielding tent membranes (waterproof sheets).
[0011] The heat-shielding tent membrane structure of the present invention, which has excellent weather resistance, preferably has a thin film layer containing zinc oxide or a mixture of titanium oxide and zinc oxide formed on the (surface) thermoplastic resin layer, and the zinc oxide and titanium oxide have a primary average particle size of 10 to 50 nm and a coating layer on the particle surface. Due to the presence of this thin film layer, ultraviolet light penetrating the (surface) thermoplastic resin layer is scattered by the zinc oxide and / or titanium oxide particles having a primary average particle size of 10 to 50 nm, blocking the transmission of ultraviolet light, and the light resistance of the (surface) thermoplastic resin layer can be further improved by a synergistic effect with the keto / enol tautomer. In particular, zinc oxide has an excellent UVA (ultraviolet A wave) shielding effect, and titanium oxide has an excellent UVB (ultraviolet B wave) shielding effect, so that it is preferable to use a mixture of titanium oxide and zinc oxide, thereby improving the durability of the heat-shielding tent membrane (waterproof sheet). The zinc oxide and titanium oxide particles used in the present invention do not deteriorate the thermoplastic resin layer in which the photocatalytic activity is sealed by surface treatment.
[0012] In the heat-shielding tent film structure having excellent weather resistance of the present invention, a thin film layer mainly composed of an organosilicate compound or a sol-gel condensate of an organic silane compound containing a silanol group is formed on the (surface) thermoplastic resin layer, and this thin film layer preferably contains one or more photocatalytic metal oxides selected from titanium oxide, titanium peroxide, zinc oxide, tin oxide, strontium titanate, tungsten oxide, bismuth oxide, and iron oxide. By disposing such a thin film layer on the (surface) thermoplastic resin layer, the photocatalytic metal oxide contained in the thin film layer exhibits photocatalytic activity by ultraviolet excitation. This photocatalytic activity contributes to the long-term durability of the thermoplastic resin layer by acting as a self-cleaning action to remove attached foreign matter such as soot and dust stains. At this time, the ultraviolet light received by the heat-shielding tent film structure having excellent weather resistance of the present invention penetrates the thin film layer and reaches the thermoplastic resin layer, but in the thin film layer, a part of the ultraviolet energy penetrating is consumed by the activation of the photocatalytic metal oxide, so that the ultraviolet energy reaching the (surface) thermoplastic resin layer located below is attenuated. Therefore, disposing the thin film layer on the (surface) thermoplastic resin layer serves to protect the thermoplastic resin layer, and thus contributes to extending the service life of the heat-shielding tent membrane structure having excellent weather resistance. Effect of the Invention
[0013] The present invention makes it possible to obtain a heat-shielding tent membrane structure with improved durability. In other words, it is possible to provide a heat-shielding tent membrane structure that can maintain a clean appearance for a long period of time due to its excellent weather resistance (reduction of ultraviolet degradation) and mold resistance (algae). Specifically, it is ideal for long-term (10 to 15 years) tent structures such as indoor sports facilities, event pavilions, traveling circuses, planetariums, and tent warehouses, and can also be used for applications lasting less than 10 years, such as architectural protection (soundproofing) sheets, pergola shades (membrane ceilings), facade sheets, lift-up sheet shutters, partition sheets, truck hoods, outdoor waterproof sheets, and house-top tents. In particular, the extension of the durability of the heat-shielding tent membrane reduces the frequency of disposal (i.e., replacement), and at the same time reduces the production volume of membrane materials, thereby reducing the consumption of petrochemical resources that cause carbon dioxide emissions, and contributing to the conservation of a sustainable global environment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The heat-shielding tent membrane structure of the present invention (hereinafter referred to as "heat-shielding tent membrane structure") having excellent weather resistance is a tent membrane structure in which a waterproof sheet is attached to the outer periphery of the side walls of a frame structure constituting a space, and to the canopy, and the waterproof sheet is a connected and sewn product of a plurality of flexible laminates each having a "(surface) thermoplastic resin layer / fabric / (back) thermoplastic resin layer" configuration, and at least the (surface) thermoplastic resin layer contains surface-treated titanium oxide particles having a primary average particle size of 0.4 to 1.2 μm, a keto / enol type tautomer, and an anti-fungal (algae) agent as essential components, and the thermoplastic resin layer contains a specific zinc oxide, or a mixture of a specific titanium oxide and a specific zinc oxide. Further included are embodiments in which a thin film layer containing a keto / enol type tautomer and an N-OR type hindered amine is formed on a (surface) thermoplastic resin layer; an embodiment in which a thin film layer containing a specific zinc oxide or a mixture of a specific titanium oxide and a specific zinc oxide is formed on a (surface) thermoplastic resin layer; and an embodiment in which a thin film layer mainly composed of a sol-gel condensate is formed on a (surface) thermoplastic resin layer, and a photocatalytic metal oxide is contained within this thin film layer.Depending on factors such as solar radiation conditions, location conditions, and shape of the tent membrane structure, it is possible to overcome unfavorable conditions by using multiple of these embodiments in one heat-shielding tent membrane structure to share functions.
[0015] The waterproof sheet, which is a part of the heat-shielding tent membrane structure of the present invention, is an extension of a plurality of flexible laminates (tarpaulin or waterproof canvas) consisting of a "(surface) thermoplastic resin layer / fabric / (back) thermoplastic resin layer" structure, which are connected together. The thermoplastic resin constituting the (surface and back) thermoplastic resin layers is a thermoplastic resin having a Shore A hardness of about 35 to 85, such as soft vinyl chloride resin (mixed with plasticizer), vinyl chloride copolymer resin, chlorinated vinyl chloride resin, olefin resin (PE, PP), olefin copolymer resin, ethylene-vinyl acetate copolymer resin (EVA), ethylene-(meth)acrylic acid (ester) copolymer resin, urethane resin, vinyl acetate copolymer resin, styrene copolymer resin, polyester copolymer resin, or fluorine-containing copolymer resin, or an elastomer, and two or more of these may be blended in a compatible or semi-compatible state, or may be a multi-layered film or multi-layered coating of two or more kinds. An elastomer is a block copolymer resin consisting of two or more monomers, and is a flexible resin in which each block component constitutes a hard segment and a soft segment. The tarpaulin for tent membrane structures is a flexible laminate having a thickness of 0.5 to 1.5 mm, in which a thermoplastic resin composition film is laminated on both sides of a fabric as a thermoplastic resin layer (front and back), and the thermoplastic resin composition film is most preferably made of soft polyvinyl chloride resin (containing a plasticizer), which is excellent in processability, flexibility, abrasion resistance, weather resistance, flame retardancy, etc. The waterproof canvas for tent membrane structures is a flexible laminate having a thickness of 0.3 to 0.8 mm, in which a liquid thermoplastic resin composition is impregnated and coated on both sides of a fabric, which is then solidified into a film to form a thermoplastic resin layer (front and back), and the thermoplastic resin composition is most preferably made of soft polyvinyl chloride resin (paste sol containing a plasticizer), which is excellent in processability, flexibility, abrasion resistance, weather resistance, flame retardancy, etc.
[0016] The primary average particle diameter of the surface-treated titanium oxide particles contained as an essential component in the (front surface, or front surface and back surface) thermoplastic resin layer is preferably 0.4 to 1.2 μm. Titanium oxide as a white pigment has a particle diameter of 0.2 to 0.4 μm, which is about 1 / 2 the wavelength of light, to maximize scattering in the visible light region (400 to 700 nm), thereby obtaining high concealing properties. On the other hand, by increasing the particle diameter to 0.4 to 1.2 μm, the concealing properties decrease, but the reflecting effect in the near-infrared region (780 to 2500 nm), which accounts for about 50% of solar energy, is increased, thereby obtaining a heat shielding effect superior to that of pigment titanium oxide. The primary average particle diameter is preferably 0.9 to 1.1 μm, and the shape of these surface-treated titanium oxide particles is approximately spherical, egg-shaped, bale-shaped, potato-shaped, etc., with an aspect ratio of 1:1 to 1:2. Surface-treated titanium oxide particles such as rod-shaped or square-shaped particles with minor axis diameter of 0.4 to 0.8 μm, major axis diameter of 2.0 to 4.0 μm, and aspect ratio of 1:5 to 1:10 can also be used in combination. If the surface treatment is not performed, the photocatalytic activity will cause radical attack on the thermoplastic resin of the thermoplastic resin layer, resulting in deterioration. The surface treatment performed on the titanium oxide particles is for preventing aggregation, improving dispersibility, and sealing the photocatalytic activity of the titanium oxide particles, and is a surface treatment with one or more metal oxides (7 options) selected from aluminum oxide, zirconium oxide, silicon oxide, and aluminum hydroxide. In addition to the surface treatment with these metal oxides, a multi-layer surface treatment may be performed in which a silane coupling agent, saturated alkyl titanate, saturated alkyl silane, polysiloxane, acrylic silicone, and metal soap (metal salt of long-chain fatty acid such as stearic acid and lauric acid and metal such as barium and zinc) are applied in one layer or two layers. Such surface treatment further improves aggregation prevention and dispersibility. The amount of the surface-treated titanium oxide particles contained in the thermoplastic resin layer is 3 to 20 parts by mass, and preferably 5 to 12 parts by mass, per 100 parts by mass of the thermoplastic resin.
[0017] The amount of the keto / enol tautomer contained as an essential component in the (front surface, or front and back surface) thermoplastic resin layer is 0.1 to 10 parts by mass, preferably 0.2 to 5 parts by mass, relative to 100 parts by mass of the thermoplastic resin constituting the thermoplastic resin layer, and the keto / enol tautomer is one or more selected from benzotriazole tautomers, triazine tautomers, and diphenyl ketone tautomers. Here, the use of multiple keto / enol tautomers includes combinations of different systems and variations of combinations in the same system. The keto / enol tautomer is an organic compound that can be reversibly converted between R2-CH-(C=O)-R1 (keto isomer) and R2-C=CH(OH)-R1 (enol isomer). Benzotriazole tautomers exist in enol and keto forms. The enol isomer (Ia) is an organic compound [Chemical formula 1] having a skeleton of a benzene ring (which may have one or two groups selected from a C1-C10 alkyl group, a C4-C10 branched alkyl group, and an alkyl-substituted benzyl group) having hydroxyl groups (1-2 groups) / ketone groups (0 groups) and a CN bond between a benzotriazole ring (which may have a chlorine group), and specifically has a structure having a hydroxyl group at the 2-position of the benzene ring, a structure having a hydroxyl group at the 2-position or any one of the 3-5-positions of the benzene ring, or a structure having a hydroxyl group at the 2-position of the benzene ring and one or two groups selected from an alkyl group, a branched alkyl group, and an alkyl-substituted benzyl group at the 3-position and / or the 5-position. The keto isomer (IIa) is an organic compound [Chemical formula 2] having as its main skeleton a CN bond between one benzene ring (which may have any of a C1-C10 alkyl group, a C4-C10 branched alkyl group, or an alkyl-substituted benzyl group) having 0-1 hydroxyl group / 1 ketone group and a benzotriazole ring (which may have a chlorine group), specifically a structure having a ketone group at the 2-position of the benzene ring, a structure having a ketone group at the 2-position and a hydroxyl group at any of the 3-5-positions of the benzene ring, or a structure having a ketone group at the 2-position and an alkyl group, a branched alkyl group, or an alkyl-substituted benzyl group at the 3- and / or 5-position of the benzene ring.The keto and enol isomers are repeatedly converted to each other, and both isomers coexist in equilibrium. Benzotriazole compounds having a molecular weight of 250 to 700, particularly hydroxyphenylbenzotriazole derivatives, are preferred as enol isomers. In the thermoplastic resin layer, the benzotriazole tautomers are repeatedly converted to the enol isomer (Ia) [Chemical formula 1] and the keto isomer (IIa) [Chemical formula 2] by the excitation of solar (ultraviolet) energy, and the ultraviolet energy is converted into molecular vibration energy of the conversion and released outside the system, thereby attenuating the deterioration damage caused by ultraviolet rays. The ultraviolet attenuation effect of the thermoplastic resin layer greatly works to extend the service life of the heat-shielding tent membrane structure having excellent weather resistance of the present invention. Here, the alkyl-substituted benzyl group means a benzyl group "C6H6-CH2-" substituted with an alkyl group "C6H6-CR1R2-" (R1 and R2 are C1 to C10 alkyl groups). Benzotriazole tautomers can also be used in the form grafted onto the side chains of acrylic polymers. [ka] R is a hydroxyl group, an alkyl group, a branched alkyl group, or an alkyl-substituted benzyl group. One or more selected from [ka] R is a hydroxyl group, an alkyl group, a branched alkyl group, or an alkyl-substituted benzyl group. One or more selected from
[0018] In addition, triazine tautomers exist in enol and keto forms, and the enol isomer (Ib) is an organic compound [Chemical formula 3] having a main skeleton of a CC bond between 1 to 3 benzene rings (which may have a C1 to C10 alkyloxy group) with hydroxyl group (1 to 2) / ketone group (0) and a 1,3,5-triazine ring (which may have an alkyl (1 to 2) substituted phenyl group and / or a hydroxyl group (1 to 2) substituted phenyl group), specifically, a structure having a hydroxyl group at the 2nd position of the benzene ring, a structure having hydroxyl groups at the 2nd and 4th positions of the benzene ring, a structure having a hydroxyl group at the 2nd position of the benzene ring and an alkyloxy group at the 4th position, an alkyl (1 to 2) substituted phenyl group at the 2nd or 4th position, or a hydroxyl group ...2nd and 4th position. The keto isomer (IIb) is an organic compound [Chemical formula 4] having a skeleton of a CC bond between 1 to 3 benzene rings (which may have C1 to C10 alkyloxy groups) with hydroxyl groups (0 to 1) / ketone groups (1), and a 1,3,5-triazine ring (which may have alkyl (1 to 2) substituted phenyl groups and / or hydroxyl groups (1 to 2) substituted phenyl groups). Specifically, the benzene ring has a structure having a ketone group at the 2-position, a structure having a ketone group at the 2-position and a hydroxyl group at the 4-position, a structure having a ketone group at the 2-position and an alkyloxy group at the 4-position, the alkyl (1 to 2) substituted phenyl group at the 2-position or 4-position, or the 2- and 4-positions, and the hydroxyl group (1 to 2) substituted phenyl group at the 2-position or 4-position or the 2- and 4-positions. The keto and enol isomers are repeatedly converted to each other, and the two isomers coexist in equilibrium. In particular, triazine compounds having a molecular weight of 250 to 700, particularly hydroxyphenyl-1,3,5-triazine derivatives, are preferred as enol isomers. In the heat shielding layer, the triazine tautomers are repeatedly converted to the enol isomer (Ib) [Chemical formula 3] and the keto isomer (IIb) [Chemical formula 4] by the excitation of solar light (ultraviolet light) energy, and the ultraviolet light energy is converted into molecular vibration energy of the conversion and released outside the system, thereby attenuating the deterioration damage caused by ultraviolet light. The ultraviolet light attenuation effect of the thermoplastic resin layer greatly contributes to the extension of the service life of the heat shielding tent membrane structure having excellent weather resistance of the present invention.Specifically, the alkyloxy group is a methoxy group, an ethoxy group, a propoxy group, a butoxy group, a tert-butyl group, a pentyloxy group, etc. In addition, the triazine tautomer can be used in the form grafted onto the side chain of an acrylic polymer. [ka] R1 is a hydroxyl group and / or an alkyloxy group. R2 and R3 are alkyl-substituted phenyl groups and / or hydroxyl-substituted phenyl groups. [ka] R1 is a hydroxyl group and / or an alkyloxy group. R2 and R3 are alkyl-substituted phenyl groups and / or hydroxyl-substituted phenyl groups.
[0019] Diphenyl ketone tautomers exist as enol and keto types, and the enol isomer (Ic) is an organic compound with a main skeleton in which two benzene rings, each with hydroxyl groups (1-2), ketone groups (0), and alkyloxy groups (0-1), are linked by a C=O bond [Chemical Formula 5]. Specific examples include a structure with a hydroxyl group at the 2nd position of the benzene ring, a structure with hydroxyl groups at the 2nd and 4th positions of the benzene ring, and a structure with a hydroxyl group at the 2nd position and an alkyloxy group at the 4th position of the benzene ring. In addition, the keto type isomer (IIc) is an organic compound [Chemical formula 6] having a main skeleton in which one benzene ring (A) having a hydroxyl group (0-1), a ketone group (1), and an alkyloxy group (0-1) and one benzene ring (B) having a hydroxyl group (1-2), a ketone group (0), and an alkyloxy group (0-1) are linked by a C=O bond. Specific examples include a structure having a ketone group at the 2nd position of the benzene ring (A), a structure having a ketone group at the 2nd position and a hydroxyl group at the 4th position of the benzene ring (A), a structure having a ketone group at the 2nd position and an alkyloxy group at the 4th position of the benzene ring (A), a structure having a hydroxyl group at the 2nd position of the benzene ring (B), a structure having hydroxyl groups at the 2nd and 4th positions of the benzene ring (B), and a structure having a hydroxyl group at the 2nd position and an alkyloxy group at the 4th position of the benzene ring (B). A diphenyl ketone compound having a molecular weight of 200 to 400, in which both isomers, keto type and enol type, are repeatedly converted to each other and coexist in equilibrium, is particularly preferred as an enol type, hydroxydiphenyl ketone derivative. Inside the thermoplastic resin layer, the diphenyl ketone tautomer is repeatedly converted to the enol type isomer (Ic) [Chemical formula 5] and the keto type isomer (IIc) [Chemical formula 6] by sunlight (ultraviolet light) energy, and the ultraviolet light energy is converted into molecular vibration energy of the conversion and released outside the system, thereby attenuating the deterioration damage caused by ultraviolet light. The ultraviolet light attenuation effect of the thermoplastic resin layer greatly works to extend the service life of the heat-shielding tent membrane structure having excellent weather resistance of the present invention. Specifically, the alkyloxy group is a methoxy group, an ethoxy group, a propoxy group, a butoxy group, a tert-butyl group, a pentyloxy group, etc. Also, the diphenyl ketone tautomer can be used by grafting it to the side chain of an acrylic polymer. [ka] R1 and R2 are hydroxyl groups and / or alkyloxy groups. [ka] R1 and R2 are hydroxyl groups and / or alkyloxy groups.
[0020] The antifungal (algae) agent contained as an essential component in the thermoplastic resin layer is a functional group that has an effect of inhibiting oxidative phosphorylation, inhibiting the electron transport system, inhibiting -SH groups, inhibiting DNA synthesis, inhibiting cell epidermal function, inhibiting lipid metabolism, forming a chelate, etc. against the cell walls, cell membranes, cytoplasm, and cell nuclei of mold, algae, bacteria (gram positive and gram negative), fungi, etc., such as -Cl, -Br, -F, -I, -S-, -(S)n-, -NO2, -CF3, -SCN, -NCS, -SCF3, -CHI2, -CH2Cl, -CCl3, These are compounds having the groups -SCCl3, -OCCl3, =CHCCl3, -CI=CI2, -CI=CIBr, -CH2C≡CI, -OCH2C≡Cl, =NC(S)S-, -NHCOC≡Cl, -CO-N(OCH3)-, -CO-NR-CO-, -NSCCl3, -NSCCl2F, -SO2-CH3, -SO2-S-CH3, -SO2C6H4CH3, -NC6H4(p-CH3)SO2C6H4(p-CH3), and -NC6H4(p-CH3)SON(CH3)2. These antifungal (algae) agents include organic compounds such as imidazole compounds, thiazole compounds, N-haloalkylthio compounds, pyridine compounds, pyrithione compounds, isothiazolin compounds, triazine compounds, and organometallic compounds, and it is preferable to use at least one selected from these compounds in an amount of 0.01 to 5 parts by mass, particularly 0.1 to 2.0 parts by mass, per 100 parts by mass of the thermoplastic resin constituting the thermoplastic resin layer. In addition, by using them in combination with inorganic antifungal (algae) agents such as silver ion-supported zeolite and copper ion-supported zeolite, the antifungal (algae) effect is mainly due to the organic compounds in the early to middle period, and the effect is mainly due to the inorganic antifungal (algae) agent in the middle to late period, so that the overall aesthetic durability can be extended.
[0021] Specific examples of imidazole compounds include 2-(4-thiazolyl)-benzimidazole (TBZ), 2-(carbomethoxyamino)benzimidazole (BCM), and 1-(butylcarbamoyl)-2-benzimidazolecarbamate methyl. Examples of thiazole compounds include 2-n-octyl-4-isothiazolin-3-one, 2-mercaptobenzothiazole, 2-(thiocyanomethylthio)benzothiazole, and 2-(thiocyanomethylsulfonyl)benzothiazole. Examples of N-haloalkylthio compounds include N-(fluorodichloromethylthio)phthalimide, N-trichloromethylthiotetrahydrophthalimide, N-(trichloromethylthio)-4-cyclohexane 1,2-dicarboximide, and N,N-dimethyl-N'-(fluorodimethylthio)-N'-phenylsulfamide. Examples of pyridine compounds include 2,3,5,6-tetrachloro-4-(methylsulfonyl)pyridine, pyrithione compounds such as zinc bis(pyridine-2-thiol-1-oxide) (abbreviated as ZPT), sodium (2-pyridinethiol-1-oxide), and 2,2'-dithio-bispyridine-1-oxide, and isothiazoline compounds such as 1,2-benzoisothiazolin-3-one and 2-n-octyl-4-isothiazolyl-3-one. , 2-trichloromethylthio-4-isothiazolin-3-one, triazine compounds such as hexahydro-N,N',N"-tris(2-hydroxyethyl)-S-triazine, hexahydro-N,N',N"-triethyl-S-triazine, and organometallic compounds such as 10,10'-oxybisphenoxyarsine (abbreviated as OBPA), 8-oxyquinoline copper, and 2-ethylhexanoate nickel. From the viewpoint of improving service life, it is particularly preferable to use sustained-release types of these anti-mold (algae) agents supported on inorganic porous fine particles such as silica, zeolite, and diatomaceous earth, or on the micropores of cyclodextrin.
[0022] As an embodiment of the heat-shielding tent film structure of the present invention, the thermoplastic resin layer (on the front surface, or on the front surface and the back surface) may further contain zinc oxide or a mixture of titanium oxide and zinc oxide as an ultraviolet shielding material. The zinc oxide and titanium oxide are preferably those having a coating layer on the particle surface and a primary average particle size of 0.3 μm or less. This allows zinc oxide or zinc oxide and titanium oxide particles having a primary average particle size of 0.3 μm or less (0.1 μm to 0.3 μm) to enter the gaps generated between the surface-treated titanium oxide particles having a primary average particle size of 0.4 to 4.0 μm contained in the thermoplastic resin layer, and the surface area of the zinc oxide and titanium oxide particles having such particle sizes is increased, thereby scattering ultraviolet rays penetrating into the thermoplastic resin layer and effectively shielding the transmission of ultraviolet rays. This ultraviolet shielding effect further improves the light resistance of the thermoplastic resin layer through a synergistic effect with the keto / enol tautomer. In particular, zinc oxide has an excellent UVA (ultraviolet A wave) shielding effect, and titanium oxide has an excellent UVB (ultraviolet B wave) shielding effect, so it is preferable to use a mixture of titanium oxide and zinc oxide with a mass ratio of 10:6 to 6:10, and particularly a mixture of 10:10. The zinc oxide and titanium oxide particles used in the present invention are preferably those whose photocatalytic activity has been sealed by surface treatment. If no surface treatment is applied, the thermoplastic resin of the thermoplastic resin layer will be deteriorated by radical attack due to the photocatalytic activity. The surface treatment applied to the zinc oxide particles and titanium oxide particles is for preventing aggregation, improving dispersibility, and sealing the photocatalytic activity of the titanium oxide particles, and is a surface treatment with one or more metal oxides (7 options) selected from aluminum oxide, zirconium oxide, and silicon oxide. Further, on top of the surface treatment with these metal oxides, a multi-layer surface treatment may be applied in which a single layer of one type or two layers of two types of silane coupling agents, saturated alkyl titanates, saturated alkyl silanes, polysiloxanes, acrylic silicones, and metal soaps (metal salts of long-chain fatty acids such as stearic acid and lauric acid with metals such as barium and zinc) are applied as a further surface treatment. Such surface treatments further improve the prevention of aggregation and the dispersibility.The amount of surface-treated zinc oxide and / or surface-treated titanium oxide particles with an average primary particle diameter of 0.3 μm or less (0.1 μm to 0.3 μm) contained in the thermoplastic resin layer is 3 to 20 parts by mass, preferably 5 to 12 parts by mass, per 100 parts by mass of the thermoplastic resin.
[0023] As an embodiment of the heat insulating tent membrane structure of the present invention, a benzotriazole tautomer, a triazine tautomer, and a diphenylketone tautomer are provided on a (surface) thermoplastic resin layer. N series A thin film layer containing one or more keto / enol tautomers selected from the above tautomers and N-OR hindered amine can be formed. The amount of the keto / enol tautomer contained in the thin film layer is preferably 1 to 25 parts by mass, particularly 3 to 10 parts by mass, based on 100 parts by mass of the thermoplastic resin binder of the thin film layer. The amount of the N-OR hindered amine contained in the thin film layer is preferably 0.5 to 12 parts by mass, particularly 1 to 6 parts by mass, based on 100 parts by mass of the thermoplastic resin binder of the thin film layer. Examples of the thermoplastic resin binder include acrylic resins, urethane resins, fluorine-based copolymer resins, combinations of acrylic resins / urethane resins, and combinations of acrylic resins / fluorine-based copolymer resins. The thickness of the thin film layer is preferably 1 to 20 μm, particularly 3 to 12 μm. The thin film layer can be formed by selecting from known coating methods such as gravure coating, wire bar coating, kiss coating, and clearance coating.
[0024] The acrylic resin to be the binder of the thin film layer may be a polymer or copolymer resin of one or more monomers selected from acrylic acid alkyl esters having an alkyl group with 1 to 18 carbon atoms and methacrylic acid alkyl esters having an alkyl group with 1 to 18 carbon atoms, or may be a copolymer of ethylenically unsaturated carboxylic acids, amide compounds, epoxy group-containing (meth)acrylic acids, α-olefins, vinyl ethers, alkenyls, vinyl esters, aromatic vinyl compounds, etc. with the above acrylic monomers, or an acrylic / silicon copolymer resin copolymerized with organosiloxanes. Examples of urethane resins include aromatic polyurethanes (esters, ethers, polycarbonates), aliphatic polyurethanes (esters, ethers, polycarbonates), and alicyclic polyurethanes (esters, ethers, polycarbonates), with aliphatic polyurethanes and alicyclic polyurethanes being preferred in terms of light fastness, and ether and polycarbonate urethane resins being particularly preferred in terms of weather fastness (hydrolysis resistance). Also usable are urethane / silicon-based graft copolymer resins and urethane / fluorine-based graft copolymer resins. The fluorine-based copolymer resins include copolymers obtained by copolymerizing two or more fluorine atom-containing monomers such as vinyl fluoride, vinylidene fluoride, trifluoroethylene, tetrafluoroethylene, chlorotrifluoroethylene, and hexafluoropropylene, and fluoroolefin copolymers obtained by copolymerizing the above-mentioned fluorine atom-containing monomers with vinyl monomers (β-methyl-β-alkyl-substituted-α-olefins, alkyl vinyl ethers, alkyl allyl ethers, vinyl group-containing esters, etc.). These are preferably copolymers containing hydroxyl groups and carboxyl groups in the molecular structure that generate crosslinking sites when used in combination with reactive compounds such as isocyanate compounds, aziridine compounds, oxazoline compounds, and carbodiimide compounds.In particular, the isocyanate compound is preferably an aliphatic compound or an alicyclic compound, and examples of the usable compounds include hexamethylene diisocyanate, isophorone diisocyanate, and trimers thereof (isocyanurate type, trimethylpropane type, biuret type), and blocked isocyanates thereof. As the oxazoline compound, a polymer-type crosslinking agent (emulsion type) having an oxazoline group on the side chain of an acrylic resin (acrylic copolymer resin, acrylic / styrene copolymer resin) can also be used.
[0025] The keto / enol tautomers can be the same as those described in paragraphs
[0017] to
[0019] of the specification. The N-OR hindered amine compounds have at least one, preferably two, or preferably four, or preferably six hindered amine structures in their molecular structure, and are particularly effective in improving the light resistance of vinyl chloride resins. The N-position of the hindered amine structure shown in the following formula [Chemical Formula 7] has one or more substituents selected from an alkoxy group having 2 to 18 carbon atoms or a cycloalkoxy group having 5 to 12 carbon atoms, and the molecular weight of these is 200 to 400 (one hindered amine structure), 400 to 700 (2 to 3 hindered amine structures), 700 to 1000 (4 to 5 hindered amine structures), or 1000 to 2500 (6 or more hindered amine structures), which are excellent in terms of residual retention in a thin film layer and are preferred. [ka] In the above [Chemical formula 7], R1, R2, R3 and R4 are each independently a) a hydrogen atom, b) a straight chain alkyl group or a branched alkyl group having 1 to 20 carbon atoms, c) the alkyl group of the above b) containing one or more of -O-, -S-, -SO-, -SO2-, -CO-, -COO-, -OCO-, -CONR-, -NRCO- or -NR-, d) an alkenyl group having 3 to 20 carbon atoms, e) an aryl group having 6 to 10 carbon atoms, f) an aryl group having 1 to 3 substituents selected from an alkyl group having 1 to 20 carbon atoms, a cycloalkyl group having 5 to 12 carbon atoms, and a phenylalkyl group having 7 to 15 carbon atoms, and the like. As the N-OR type hindered amine compound used in the heat-shielding tent membrane structure having excellent weather resistance of the present invention, it is particularly preferable that R1, R2, R3 and R4 are all hydrogen or all methyl groups. R5 is i) an alkyl group having 2 to 18 carbon atoms, i.e., one in which the N-position of the hindered amine structure is substituted with an alkoxy group having 2 to 18 carbon atoms, particularly preferably an alkoxy group having 6 to 12 carbon atoms, or ii) a cycloalkyl group having 5 to 12 carbon atoms, i.e., one in which the N-position of the hindered amine structure is substituted with a cycloalkoxy group having 5 to 12 carbon atoms, preferably a cycloalkoxy group having 5, 6 or 8 carbon atoms, particularly preferably a cyclohexyloxy group.
[0026] Specific examples of these N-OR type hindered amine compounds are compounds having at least one substituent R5 selected from an alkyl group having 2 to 18 carbon atoms or a cycloalkyl group having 5 to 12 carbon atoms at the N-position of the hindered amine structure [Chemical formula 7]. These include bis(1-undecaoxy-2,2,6,6-tetramethylpiperidin-4-yl)carbonate, 4,4'-hexamethylene-bis(N-OR5-2,2,6,6-tetramethylpiperidine) and 2,4-dichloro Polycondensation products of 1-(2-hydroxyethyl)-N-OR5-2,2,6,6-tetramethyl-4-hydroxypiperidine and succinic acid: Polycondensation products of N,N',N'',N'''-tetrakis[4,6-bis(butyl-(N-OR5-2,2,6,6-tetramethylpiperidin-4-yl)amino)-s-triazin-2-yl]-1,10-diamino-4,7-diazadecane; 4,4'-hexamethylene-bis(N-OR5-2,2 ,6,6-tetramethylpiperidine) and 2,4-dichloro-6-morpholino-s-triazine;Poly[methyl 3-(N-OR5-2,2,6,6-tetramethylpiperidin-4-yloxy)propyl]siloxane;Bis(N-OR5-2,2,6,6-tetramethylpiperidin-4-yl)cyclohexylenedioxydimethylmalonate;Bis(N-OR5-2,2,6,6-tetramethyl-4-piperidyl)[[3,5bis(1,1-dimethylethyl)-4-hydro butyl malonate;bis(N-OR5-2,2,6,6-tetramethyl-4-piperidyl) sebacate;1,3,5-tris{N-cyclohexyl-N-[2-(N-OR5-2,2,6,6-tetramethylpiperazin-3-one-4-yl)ethyl]amino-s-triazine;Polycondensation products of 4,4'-hexamethylene-bis(N-OR5-2,2,6,6-tetramethylpiperidine) and 2,4-dichloro-6-cyclohexylamino-s-triazine;and poly{N-[4,6-bis(butyl-(N-OR5-2,2,6,6-tetramethylpiperidin-4-yl)amino)-s-triazin-2-yl]-1,4,7-triazanonane}-ω-N″-[4,6-bis(butyl-(N-OR5-2,2,6,6-tetramethylpiperidin-4-yl)amino)-s-triazin-2-yl]amine.
[0027] The photostabilization cycle of N-OR type hindered amine begins when N-OR type hindered amine is oxidized by oxygen, ultraviolet light, peroxide, etc. and converted to nitroxy radical (NO·), which captures alkyl radical (R·) generated by photodegradation of thermoplastic resin in thermoplastic resin layer and converts to amino ether (NOR), and then captures peroxide radical (ROO·) generated by reaction of alkyl radical (R·) with oxygen in air at N-OR part, neutralizes it to alcohol or ketone, releases it, and returns to original nitroxy radical (NO·). By repeating this cycle in nanoseconds, it is possible to suppress the chain progression of bond cleavage of thermoplastic resin caused by attack of harmful radicals. This radical neutralization cycle is the same for NH type hindered amine and N-alkyl type hindered amine, but N-OR type hindered amine is the most preferable for stabilization of light resistance of vinyl chloride resin. In the present invention, it is also possible to use N-OR type hindered amine and NH type hindered amine in combination, or N-OR type hindered amine and N-alkyl type hindered amine in combination, and the combination ratio is preferably 10:1 to 10:10, particularly 10:2 to 10:5. If the use ratio of N-OR type hindered amine in a blending system mainly composed of vinyl chloride resin is low, a significant light resistance improvement effect may not be obtained. In addition, the use ratio of keto / enol type tautomer and N-OR type hindered amine is preferably 10:1 to 10:5, particularly 10:3 to 10:4. If the use ratio of keto / enol type tautomer is low, a significant light resistance improvement effect may not be obtained.
[0028] As an embodiment of the heat-shielding tent membrane structure of the present invention, a thin film layer containing zinc oxide or a mixture of titanium oxide and zinc oxide can be formed on a (surface) thermoplastic resin layer. The zinc oxide and titanium oxide have a primary average particle size of 10 to 50 nm and a coating layer on the particle surface, and the content of zinc oxide or a mixture of titanium oxide and zinc oxide in the thin film layer is preferably 0.1 to 10 mass%, particularly preferably 0.5 to 5 mass%. Such ultrafine zinc oxide and titanium oxide are far from the particle size suitable for white pigments, so that the hiding power is reduced and the thin film layer becomes transparent, and at the same time, the surface area (specific surface area) per unit mass is increased due to the ultrafine particles, so that the UVA (ultraviolet A wave) shielding effect of zinc oxide and the UVB (ultraviolet B wave) shielding effect of titanium oxide are dramatically improved. It is preferable to use ultrafine zinc oxide and ultrafine titanium oxide in a mixture with a mass ratio of 10:6 to 6:10, particularly a mixture with a mass ratio of 10:10. For the same reason, it is preferable that the photocatalytic activity of ultrafine zinc oxide and titanium oxide is blocked by the surface treatment described in paragraph
[0016] . The thin film layer is mainly composed of an organosilicate compound or a sol-gel condensate of a silanol group-containing organosilane compound. The organosilicate compound has the chemical formula: Si n O n-1 (OR) 2(n+1)In the formula, R is an alkyl group having 1 to 10 carbon atoms (particularly a lower alkyl group having 1 to 3 carbon atoms) or an aryl group (particularly a phenyl group), n is the degree of polymerization (n-mer) that represents the number of condensed molecules of the tetrafunctional hydrolyzable silane compound and is an integer of 1 or more. Examples of compounds where n is 1 include tetramethoxysilane "Si(OCH3)4", tetraethoxysilane "Si(OC2H5)4", tetrapropoxysilane "Si(OC3H7)4", tetrabutoxysilane "Si(OC4H9)4", tetraphenoxysilane "Si(OC6H6)4", and dimethoxydiethoxysilane "Si(OCH3)2(OC2H5)2". Compounds with n of 2 or more are polymers formed by condensation of two or more molecules by the reaction between silanol groups formed by hydrolysis of tetrafunctional hydrolyzable silane compounds, and the degree of polymerization represented by n means the number of Si atoms contained in one molecule of the polymer. In the present invention, it is preferable to use a silanol group-containing silane compound obtained by hydrolysis of tetramethoxysilane or tetraethoxysilane with a degree of polymerization of 2 to 10, preferably 4 to 6, since the structure of the sol-gel condensate is finer. The concentration of the hydrolysis product of organosilicate contained in the coating liquid (water / alcohol) forming the thin film layer is preferably in the range of 0.01 to 30% by mass, particularly 0.1 to 5% by mass. In addition, the coating liquid may contain cellulose nanofibers in an amount of 1 to 10% by mass relative to the concentration of the hydrolysis product of organosilicate in order to impart flexibility and bendability to the thin film layer. The cellulose nanofibers used are short fibers having an average aspect ratio (average fiber length / average fiber diameter) of 10 to 50, an average fiber diameter of 3 nm to 100 nm, and an average fiber length of 100 μm or less, particularly 300 nm to 500 nm, and these may be chemically modified with a silane coupling agent, a boric acid compound, a phosphoric acid compound, a silicate compound, etc.
[0029] As an embodiment of the heat-shielding tent membrane structure of the present invention, a thin film layer mainly composed of an organosilicate compound or a sol-gel condensate of a silanol group-containing organic silane compound can be formed on a (surface) thermoplastic resin layer. This thin film layer preferably contains at least one photocatalytic metal oxide selected from titanium oxide, titanium peroxide, zinc oxide, tin oxide, strontium titanate, tungsten oxide, bismuth oxide, and iron oxide. This photocatalytic metal oxide preferably has an average particle size of 50 nm or less, particularly 20 nm or less, and with this particle size, the specific surface area becomes large and sufficient photocatalytic activity is exhibited, thereby decomposing oily soot and dust stains and allowing self-cleaning removal by rainfall. This allows the heat-shielding effect of the heat-shielding tent membrane structure of the present invention to be stably maintained for a long period of time. To form this thin film layer, a photocatalytic metal oxide in a sol state is used, and it is preferable to include 10 to 50 mass % of the thin film layer. Metals and metal oxides such as Pt, Rh, RuO2, Nb, Cu, Sn, NiO, etc. can be added to these photocatalytic metal oxides as synergistic agents. The ultraviolet light received by the heat-shielding tent membrane structure of the present invention passes through the thin film layer and then through the thermoplastic resin layer, but in the thin film layer, a part of the ultraviolet energy passing through is consumed for activating the photocatalytic metal oxide, so that the ultraviolet energy reaching the thermoplastic resin layer located below is attenuated. Therefore, disposing the thin film layer on the thermoplastic resin layer protects the thermoplastic resin layer, and thus contributes to extending the service life of the heat-shielding tent membrane structure. Since the photocatalytic metal oxide has the function of decomposing organic matter by oxidation-reduction due to photocatalytic activity, the thin film layer is mainly composed of an organosilicate compound or a sol-gel condensate of a silanol group-containing organosilane compound, which improves the resistance of the thin film layer to abrasion loads and enables long-term use of the heat-shielding tent membrane structure.In addition, the thin film layer contains 1 to 10 mass% of a silane coupling agent (aminosilane, vinylsilane, epoxysilane, methacrylsilane, acrylicsilane, chlorosilane, mercaptosilane, isocyanurate silane, isocyanate silane, etc.), and the hydrolyzate of the silane coupling agent is bonded and intervenes between the sol-gel condensate and the photocatalytic metal oxide, thereby further improving the bending resistance and resistance to abrasion load of the thin film layer. The thin film layer has a thickness of 10 nm to 5 μm, and the photocatalytic metal oxide contained in the thin film layer is 10 to 50 mass%, preferably 5 to 35 mass%. In addition, self-cleaning is an effect in which organic residues such as dirt (soot, tar), mold, and algae decomposed by photocatalytic activity are washed away by rainfall, restoring the appearance before the dirt and the like were attached. The thin film layer is mainly composed of the organosilicate compound described in paragraph
[0027] or a sol-gel condensate of a silanol group-containing organic silane compound, and may contain 0.1 to 25 mass% of an inorganic colloid (silica sol, antimony sol, alumina sol, zirconia sol, etc.) relative to the concentration of the organosilicate hydrolysis product in order to further extend the abrasion resistance and durability of the thin film layer.
[0030] The thermoplastic resin layer of the heat-shielding tent membrane structure of the present invention may contain any additives as necessary. Additives that contribute to improving weather resistance include antioxidants (hindered phenols, phosphite, sulfur, vitamin E, etc.), matting agents such as silica, calcium silicate, magnesium silicate, and aluminum silicate, colorants such as organic pigments, inorganic pigments, aluminum luster pigments, pearl pigments, and dyes, antistatic agents such as surfactants, ionic liquids, conductive carbon, carbon nanotubes, and fullerenes, flame retardants such as sepiolite, montmorillonite, and smectite, abrasion resistance strengthening agents such as isocyanates, acrylates, epoxies, silane coupling agents, and silicone oils, and other antibacterial and antiviral agents. The (front and back) thermoplastic resin layers can be obtained, for example, by melt-rolling (stretching) a soft vinyl chloride resin compound to a thickness of 0.1 mm to 1.0 mm using a calendar method or a T-die extrusion method. Alternatively, for example, a soft polyvinyl chloride resin paste sol can be coated or dipped, and then heated to gel, thereby forming a coating having a thickness of 0.05 mm to 0.5 mm.
[0031] The fabric used in the heat-shielding tent membrane structure of the present invention is preferably a woven fabric, and contains one or more types of yarn selected from multifilament yarn, staple fiber spun yarn, and covering yarn, and is either 1) a woven fabric consisting of warp yarn and weft yarn, or 2) a triaxial fabric consisting of warp yarn and upper left / upper right bias yarn, or 3) a quadriaxial fabric consisting of warp yarn, weft yarn, and upper left / upper right bias yarn. In particular, plain weave fabrics made of warp and weft threads, twill fabrics (regular twill weaves such as 2x2, 3x3, 4x4, and irregular twill weaves such as 3x2, 4x2, 4x3, 5x3, 2x3, 2x4, 3x4, 3x5), twill fabrics (having a minimum structural unit of at least three warp and weft threads: 3-sheet twill, 4-sheet twill, 5-sheet twill, 6-sheet twill, etc.), satin fabrics (having a minimum structural unit of at least five warp and weft threads: regular twill with 2-step, 3-step, 4-step, 5-step, etc.), and other imitation gauze fabrics and twisted fabrics (sha fabrics, ro fabrics) can be used. In particular, when triaxial or quadriaxial fabrics are used, the intersections between the threads become complex and dense, and the network that spreads in multiple directions increases the propagation of external stresses such as bending and flapping applied to the weather-resistant heat-shielding tent membrane structure, dispersing and deflecting the stress over a wide area to mitigate damage and at the same time increase resistance to external forces such as tearing. The fabric weight is 100-500g / m 2 The porosity (the total occupancy of the space generated by the intertwining of threads) is preferably about 6 to 25% for tarpaulin and about 0 to 10% for canvas. These woven fabrics may be subjected to known dyeing and finishing processes such as scouring, bleaching, dyeing, softening, water repellency, mildew resistance, flame resistance, and calendaring. Tarpaulin is a fabric in which a thermoplastic resin film is laminated on both sides, and canvas is a fabric in which a liquid thermoplastic resin composition is impregnated and coated on both sides, forming a film.
[0032] The yarns constituting the woven fabric (cloth) can be any fiber, such as synthetic fibers, natural fibers, semi-synthetic fibers, inorganic fibers, and mixed fibers consisting of two or more of these. Generally, however, one or more types of yarns selected from 1) multifilament yarns, 2) staple spun yarns, and 3) and covered yarns made of synthetic fibers such as polypropylene fibers, polyethylene fibers, polyvinyl alcohol fibers, polyester (polyethylene terephthalate: PET, polybutylene terephthalate: PBT, polynaphthalene terephthalate: PNT, etc.) fibers, nylon fibers, and mixed fibers (mixed and twisted) of these fibers can be used. The multifilament yarn can be a yarn having a fineness of 125 to 2000 denier (139 to 2222 dtex) obtained by stretching a long fiber spun bundle (50 to 500 filament bundle) 3 to 5 times by extruding a thermoplastic resin such as nylon or polyester from a spinneret or twisting it 10 to 200 times / m. These multifilament yarns include bulky processed yarns such as taslan yarn and woolly yarn. The short fiber spun yarn can be a roving (coarse yarn) obtained by stretching a sliver by opening and twisting a long fiber spun bundle (which may be stretched) obtained by extruding a thermoplastic resin such as nylon or polyester from a spinneret and spinning it, and then drafting and twisting the roving to a predetermined count. Examples of the twisted yarn include a single yarn or two single yarns that are aligned and twisted in an S (right) or Z (left) direction, and a two-ply yarn that is aligned and twisted in a first twist of a single yarn or two single yarns that are aligned and twisted in a second direction. The number of twists of these twisted yarns is about 200 to 2000 times / m. Examples of the covered yarn include a covered yarn in which the short fiber is wrapped around the outer periphery of the multifilament yarn bundle, and in this application, a core-sheath composite yarn is also included in the covered yarn.
[0033] In particular, a special cloth (woven fabric) can be used to improve the tensile breaking strength, tear (cut) strength, explosion-proof pressure resistance, heat resistance, and fire resistance of the heat-shielding tent membrane structure of the present invention. For this cloth, a woven fabric design mainly made of multifilament yarns such as fluororesin fibers, wholly aromatic polyester fibers, wholly aromatic polyamide fibers, etc., or a combined design with yarns made of the above-mentioned general-purpose synthetic fibers (insertion of a ripstop structure) is suitable. In addition, for applications of non-combustible materials (non-combustible membrane materials for tent structures) certified by the Minister of Land, Infrastructure, Transport and Tourism, woven fabrics mainly made of inorganic multifilament yarns such as glass fibers, silica fibers, alumina fibers, silica alumina fibers, carbon fibers, and mixed fibers thereof (mixed and twisted). In particular, in order to dramatically improve tensile breaking strength, tear (cut) strength, explosion-proof pressure resistance, heat resistance, and fire resistance, it is suitable to design a textile mainly containing yarns (multifilament yarns, staple spun yarns, covered yarns) made of one or more aromatic heterocyclic polymer fibers selected from the group consisting of polybenzimidazole (PBI)-based, polybenzoxazole (PBO)-based, polybenzothiazole (PBT)-based, and copolymers thereof (benzimidazole-benzoxazole copolymers, benzimidazole-benzothiazole copolymers, benzoxazole-benzothiazole copolymers, benzimidazole-benzoxazole-benzothiazole copolymers, and the above copolymers containing an aromatic polyamide component), or to use the textile in combination with yarns made of the above general-purpose fibers (insertion of a ripstop structure). The ripstop structure is, for example, a plain weave fabric with polyester fiber yarns as warp and weft, in which yarns made of aromatic heterocyclic polymer fibers are arranged regularly or randomly at arbitrary positions of the warp and weft, and is suitable for woven fabrics, triaxial fabrics, and quadraxial fabrics that form a lattice pattern (or irregular lattice pattern) in appearance. Specifically, in a yarn arrangement of 1,2,3,4,5...n (n is an integer) in the warp and weft groups, aromatic heterocyclic polymer fiber yarns are inserted every multiple of 10 (10,20,30...) to form a lattice pattern.In addition, in a four-axis woven fabric, any or all of the warp, weft, upper left bias yarn, and upper right bias yarn can be aromatic heterocyclic polymer fiber yarns. Specifically, the warp and weft can be aromatic heterocyclic polymer fiber yarns, and the upper left bias yarn and the upper right bias yarn can be other fiber yarns, or the upper left bias yarn and the upper right bias yarn can be other aromatic heterocyclic polymer fiber yarns, and the warp and weft can be other fiber yarns.
[0034] The tarpaulin used in the heat-shielding tent membrane structure of the present invention can be a film (sheet) having a thickness of 0.1 mm to 1.0 mm, particularly 0.15 mm to 0.3 mm, which is obtained by hot kneading a thermoplastic resin composition (particularly preferably vinyl chloride resin / plasticizer, etc.) and melt rolling it by a calendar method or a T-die extrusion method. The resin processing of the woven fabric is performed using a laminator having one or two continuous heat roll / rubber roll bonding units, a cooling roll unit, and a winding unit, and the resulting resin-processed woven fabric is hot melt-bonded by one or two passes through the laminator. Tarpaulins are produced by thermocompressing a film obtained by calendar molding onto both sides of an open-mesh fabric using a laminator, and have a configuration of "(thin film layer) / (surface) thermoplastic resin layer / fabric (multifilament yarn) / (back) thermoplastic resin layer" with a thickness of 0.5 to 1.5 mm and a mass of 500 to 2000 g / m, and can be used for membrane structures such as large tents (pavilions), circus tents, tent warehouses, membrane roofs (ceilings) for architectural spaces, and sunshade tents. The canvas is a resin-processed woven fabric produced by impregnating and coating the surface and interior of a woven fabric with a solution-type thermoplastic resin composition (particularly preferably a paste of vinyl chloride resin / plasticizer, etc.) by a coating method such as knife coating or clearance coating, and then thermally drying or heat-gelling the resulting fabric, or by dipping the woven fabric into a liquid bath filled with a solution-type thermoplastic resin composition (particularly preferably a vinyl chloride resin paste), and simultaneously pulling the fabric up and squeezing it between a pair of rubber rolls, followed immediately by thermally drying or heat-gelling the resulting fabric. The canvas is produced by a dipping method using a paste of vinyl chloride resin / plasticizer, etc., and a "(thin film layer) / (surface) thermoplastic resin layer / fabric (short fiber spun yarn) / (back) thermoplastic resin layer" embodiment with a thickness of 0.3 to 0.8 mm and a mass of 400 to 1000 g / m is suitable for use in truck hoods, truck bed sheets, house tents, sheet houses, etc. In this paragraph, "(thin film layer) / " is an optional additional layer, but is the best mode of the heat insulating tent membrane structure of the present invention in terms of extending the service life.
[0035] Tent membrane structures include indoor sports, event halls, pavilions, traveling circus tents, and tent warehouses, but we will use a tent warehouse as an example. A tent warehouse is made by attaching a waterproof sheet (sewn tarpaulin or waterproof canvas) to the outer periphery of the side walls of a frame structure that forms the space and to the canopy, and the most common roof types are arched kamaboko type and triangular gable type. The scale is one-story with an eaves height of 5m or less and a floor area of 1000m per building. 2 The Ministry of Construction has the following regulations. The method of constructing a tent warehouse is generally to assemble the columns of the truss structure that constitute the main frame on the ground in advance, erect each column, connect each column with horizontal beams and horizontal joints, hang an arch truss on the head of the erected column, complete the frame structure, and finally cover the exterior with a waterproof sheet (sewn tarpaulin or waterproof canvas). A waterproof sheet is an expanded version of a long roll of tarpaulin (or waterproof canvas) (1 to 3 m wide, 20 to 50 m long) cut to the size of the parts of the tent warehouse and connected together. The connection can be achieved by overlapping the ends of the tarpaulin (or waterproof canvas) by 2 to 10 cm, and heat welding each other's thermoplastic resin layers (the thermoplastic resin layer on the back side of the upper tarpaulin and the thermoplastic resin layer on the front side of the lower tarpaulin) using a known method such as high-frequency welding, hot air welding, or hot iron welding. The waterproof sheet is generally installed so that the lengthwise direction (wrapped direction) of the tarpaulin (or waterproof canvas) runs continuously from the left side wall to the canopy to the right side wall when facing the front of the tent warehouse. The inside of the waterproof sheet (the inside of the stitching) is treated so that grommets, hooks, ropes, etc. can be used to secure the waterproof sheet to the frame structure.
[0036] The specific examples and performance of the heat-insulating tent membrane structure of the present invention will be further described with reference to the following examples and comparative examples. The weather resistance, heat insulation property, and mold (algae) prevention property of the heat-insulating tent membrane structure were evaluated using the sheet pieces constituting the heat-insulating tent membrane structure, and the performance was applied to the performance of the heat-insulating tent membrane structure. *Examples 1 to 6 and 10 to 15 should be read as Reference Examples 1 to 6 and 10 to 15, respectively. Accelerated weathering test In accordance with JIS K5600-7-7 "General coating test methods (Part 7) Long-term durability of coating film," the discoloration of the sheet pieces (surface of the thermoplastic resin layer) was evaluated in terms of color difference ΔE (JIS Z8729) after 1000, 1500, and 2000 hours of exposure to a weathering accelerator (with the sheet pieces before acceleration as the standard). ΔE=0~2.9: 1=No coloring allowed (compliant) ΔE=3~5.9: 2=Slight coloring is observed (compliant) ΔE=6~11.9: 3=Discoloration to light brown (affects appearance) ΔE=12~19.9: 4=discolored brown (abnormal appearance) ΔE=20~: 5=Discoloration to blackish brown (appearance abnormal) <Flexural durability after accelerated weathering test> Using sheet pieces exposed to the weathering accelerator for 1000 hours, 1500 hours, and 2000 hours, a load of 1 kgf was applied to the sheet pieces by bending and kneading 500 times in accordance with JIS L1096, Section 8.19 "Abrasion strength method B (Scott method)", and the abrasion state of the (surface) thermoplastic resin layer and the presence or absence of cracks were evaluated by observing a 100x magnified image of the thermoplastic resin layer using a digital microscope (VHX-1000: Keyence Corporation). 1: No abnormalities were found in the thermoplastic resin layer (compliant) 2: Minor cracks are observed in the thermoplastic resin layer, but no peeling or falling off is observed (compliant). 3: Numerous cracks have occurred in the thermoplastic resin layer, affecting the appearance 4: Numerous cracks occurred in the thermoplastic resin layer, accompanied by peeling and falling off of cracked pieces. 5: The thermoplastic resin layer has deteriorated and fallen off, exposing the fabric. <Heat shielding rate (%)> An infrared lamp simulating sunlight was used, and the rate at which the sheet piece blocked radiant heat was taken as the heat shielding rate of the sheet and was measured according to the following test method. < Testing environment 〉 An infrared lamp (100V, 125W, Eye-R type: Iwasaki Electric Co., Ltd.) was attached to the center of the ceiling of a box-shaped structure with an inner diameter of 60cm height x 70cm width x 70cm length, which has the ability to block outside air and is airtight, and a base (8cm high) with a heat flow meter (Shortrm HFM heat flow meter: Showa Denko Co., Ltd.) sensor attached was constructed in the center of the bottom surface inside the test box. At this time, the distance from the ceiling to the tip of the infrared lamp was 22cm, and the distance from the tip of the infrared lamp to the sensor was 30cm (22cm + 30cm + 8cm = 60cm). The lamp was turned on in this environment, and the heat flow (kcal / m 2 h) every minute, and the heat flow rate qn (kcal / m 2 After the temperature inside the box-shaped structure was returned to 20°C, a test sheet (10 cm long x 10 cm wide) was placed on the base on which the sensor was attached, and a 3.5 mm thick transparent glass plate was placed on top of the test sheet. The lamp was then turned on and the heat flow rate (kcal / m 2 h) every minute, and the heat flow rate qc (kcal / m 2 h) was measured, and the thermal barrier coefficient pf (%) was calculated according to formula (2). Heat shielding rate pf(%) = [(qn-qc) / qn] × 100 (1) The higher the heat shielding rate pf (%), the higher the heat shielding effect. <Light transmittance (%)> Measurement was performed in accordance with JIS Z8722 (condition g) using a spectrophotometer CM-36dGV manufactured by Konica Minolta, Inc. <Mold-resistant> Accelerated weathering tests according to JIS K5600-7-7 were conducted for 1000 hours, 1500 hours, and 2000 hours, and an agar medium containing a spore mixture of Aspergillus niger FERM S-1 (black mold), (B) Penicillium citrinum FERM S-5 (blue mold), and (C) Cladosporium cladosporioides FERM S-8 (black mold) was dropped onto the surface of the (front) thermoplastic resin layer of the sheet piece. The mold growth was observed in a petri dish at 28°C for 7 days, and evaluated according to the following criteria. 1: No mold growth observed 2: Mold partially occurs (occupying less than 20% of the colony area) 3: Mold partially occurs (21-50% of colony area) 4: Mold has appeared in most areas (51-70% of colony area) 5: Mold has appeared over almost the entire surface (over 71% of the colony area)
[0037] [Example 1] <Fabric (1)> The fabric used was a plain weave fabric made of 1000 denier (1111 dtex) polyethylene terephthalate (PET) fiber (192 filaments) and S-twisted 50 T / m PET multifilament yarn for the warp and weft groups, with the warp group having a weave of 16 threads per inch and the weft group having a weave of 16 threads per inch. The mass of this fabric (1) was 150 g / m 2 The porosity (total of holes) was 14%. <Tarpaulin> This fabric (1) was used as a substrate, and on both sides of it, a 0.2 mm-thick calendar-molded film made of the soft vinyl chloride resin composition shown in [Formulation 1] below was used as a front and back thermoplastic resin layer, and melt-laminated by thermocompression bonding with a laminator to obtain a film with a thickness of 0.7 mm and a mass of 830 g / m. 2 The result was tarpaulin (1). [Formulation 1]: Soft polyvinyl chloride resin composition (compound) Vinyl chloride resin (degree of polymerization 1300) 100 parts by weight Diisononyl phthalate (plasticizer: Mw419) 55 parts by weight Tricresyl phosphate (flame retardant plasticizer) 10 parts by mass Epoxidized soybean oil (stabilizer and plasticizer) 5 parts by weight Barium / zinc composite stabilizer 2 parts by weight Antimony trioxide (flame retardant) 10 parts by weight Surface-treated titanium oxide particles (average primary particle size 1 μm) 10 parts by mass * Surface treatment with aluminum oxide (outermost layer treated with stearic acid) Hindered phenol antioxidant 0.5 parts by mass Benzotriazole tautomer 3 parts by mass * In the enol form, the vector of 2-hydroxyl group (1) / ketone group (0) in [Chemical formula 1] is One benzotriazole ring (5-position tert-butyl group) at C1 and one benzotriazole ring (no substituents) Organic compounds of MW267 by CN coupling with *As the keto type, in [chemical formula 2], benzene with 0 hydroxyl groups and 1 ketone group at the 2nd position One benzotriazole ring (5-position tert-butyl group) at the 1st C position and one benzotriazole ring (no substituents) CN conjugate (MW267) *1st, 2nd, 5th positions represent the carbon positions of the benzene ring. 10,10'-oxybisphenoxyarsine (mold inhibitor) 0.8 parts by mass
[0038] [Example 2] The same procedure as in Example 1 was repeated except that 3 parts by mass of the benzotriazole tautomer in [Blend 1] of Example 1 was replaced with 3 parts by mass of a triazine tautomer in [Blend 2], with a thickness of 0.7 mm and a mass of 830 g / m. 2 The result was tarpaulin (2). ※Triazine tautomers are enol forms, with the 2-hydroxyl group (1 1, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67 Organic compounds of MW367 with C-C bonds at 2, 4, and 6 positions of the 5-triazine ring *As for the keto type, in [Chemical formula 4], hydroxyl group (0) / ketone group (1) at the 2-position is benzene The 1-C of each of the three phenyl rings (butoxy group at 4-position) and the 2,4,6 of the 1,3,5-triazine ring CC bond at position C (MW367) * The 1st, 2nd, and 4th positions represent the carbon positions of the benzene ring, and the 2nd, 4th, and 6th positions of the triazine ring. indicates the carbon position, and 1, 3, and 5 positions indicate the nitrogen N position.
[0039] [Example 3] The same procedure as in Example 1 was repeated except that 3 parts by mass of the benzotriazole tautomer in [Blend 1] of Example 1 was replaced with 3 parts by mass of a diphenyl ketone tautomer [Blend 3], with a thickness of 0.7 mm and a mass of 830 g / m 2 The result was tarpaulin (3). ※Diphenyl ketone tautomers are enols, and in [Chemical formula 5], the 2-hydroxyl 1 ketone group / 1 4-octoxy group on benzene ring (other substitutions (No other substituents) One 1-position C and a benzene ring (no other substituents) are bonded through C=O. Organic compounds of MW296 * In the keto form, in [Chemical formula 6], there are 0 hydroxyl groups, 1 ketone group at the 2nd position, and 1 hydroxyl group at the 4th position. 1 C of benzene ring (without other substituents) with 1 methoxy group and 1 C of benzene ring (without other substituents) (without substituents) bonded via C=O (MW296) *1st, 2nd, and 4th positions represent the carbon positions of the benzene ring.
[0040] [Example 4] A thickness of 0.7 mm and a mass of 833 g / m were obtained in the same manner as in Example 1, except that [Blend 4] was used in which 1 part by mass of titanium oxide particles (surface-treated with aluminum hydroxide / outermost layer treated with stearic acid) having a primary average particle size of 0.2 μm and 1 part by mass of zinc oxide particles (surface-treated with aluminum hydroxide / outermost layer treated with stearic acid) having a primary average particle size of 0.2 μm were added to [Blend 1] in Example 1. 2 The result was tarpaulin (4).
[0041] [Example 5] A thickness of 0.7 mm and a mass of 833 g / m were obtained in the same manner as in Example 2, except that [Blend 5] was used in which 1 part by mass of titanium oxide particles (surface-treated with aluminum hydroxide / outermost layer treated with stearic acid) having a primary average particle size of 0.2 μm and 1 part by mass of zinc oxide particles (surface-treated with aluminum hydroxide / outermost layer treated with stearic acid) having a primary average particle size of 0.2 μm were added to [Blend 2] in Example 2. 2 The result was tarpaulin (5).
[0042] [Example 6] A tarpaulin (6) having a thickness of 0.7 mm and a mass of 833 g / m2 was obtained in the same manner as in Example 3, except that [Blend 6] was used in which 1 part by mass of titanium oxide particles (surface-treated with aluminum hydroxide / outermost layer-treated with stearic acid) having a primary average particle diameter of 0.2 μm and 1 part by mass of zinc oxide particles (surface-treated with aluminum hydroxide / outermost layer-treated with stearic acid) having a primary average particle diameter of 0.2 μm was added to [Blend 3] in Example 3.
[0043] [Example 7] The same as in Example 1, except that a thin layer (8 μm) of a fluorine-based copolymer resin containing a benzotriazole-based tautomer and an N-OR type hindered amine in a mass ratio of 3:1 was added to one surface of the tarpaulin (1) of Example 1, with a thickness of 0.7 mm and a mass of 835 g / m 2 The tarpaulin (7) was obtained. The thin film layer was formed by applying the solution of [Formulation 7] to a 120 mesh gravure roll coater. [Formulation 7]: Thin film layer Fluoroalkyl vinyl ether (containing hydroxyl group) 100 parts by mass *Paint containing 40% fluoropolymer resin by mass: Solvent toluene / MEK (1:1) Hexamethylene diisocyanate (hardening agent) 5 parts by weight Benzotriazole tautomers 6 parts by weight *The same keto / enol tautomers as in Example 1 [Chemical formula 1] / [Chemical formula 2] N-OR type hindered amine 2 parts by mass *Bis(1-undecaoxy-2,2,6,6-tetramethylpiperidin-4-yl) Carbonate (MW681) * In [Chemical formula 7], R1 to R4 are all methyl groups, and R5 is an undecyl group (-C 11 H 23 )
[0044] [Example 8] The same procedure as in Example 2 was repeated except that a thin layer (8 μm) of a fluorine-based copolymer resin containing a triazine-based tautomer and an N-OR type hindered amine in a mass ratio of 3:1 was added to one surface of the tarpaulin (2) of Example 2. The thickness was 0.7 mm and the mass was 835 g / m. 2 Tarpaulin (8) of the above formula was obtained. The thin film layer was formed by using the solution of [Blend 8] with a 120 mesh gravure roll coater. [Blend 8] is a composition in which 6 parts by weight of the benzotriazole tautomer of [Blend 7] was replaced with 6 parts by weight of the keto / enol tautomers [Chemical formula 3] / [Chemical formula 4], the same as in Example 2.
[0045] [Example 9] The same as in Example 3, except that a thin layer (8 μm) of a fluorine-based copolymer resin containing a benzophenone-based tautomer and an N-OR type hindered amine in a mass ratio of 3:1 was added to one surface of the tarpaulin (3) of Example 3, with a thickness of 0.7 mm and a mass of 835 g / m 2 Tarpaulin (9) was obtained. The thin film layer was formed by using the solution of [Blend 9] with a 120 mesh gravure roll coater. [Blend 9] is a composition in which 6 parts by weight of the benzotriazole tautomer of [Blend 7] was replaced with 6 parts by weight of the keto / enol tautomer [Chemical formula 5] / [Chemical formula 6], the same as in Example 3.
[0046] [Example 10] A thin film layer (1 to 3 μm) of a sol-gel condensate containing titanium oxide particles having a primary average particle size of 10 nm (surface-treated with aluminum hydroxide / outermost layer treated with stearic acid) and zinc oxide particles having a primary average particle size of 10 nm (surface-treated with aluminum hydroxide / outermost layer treated with stearic acid) in a 1:1 mass ratio was added to one surface of the tarpaulin (1) of Example 1, with a thickness of 0.7 mm and a mass of 835 g / m. 2 The tarpaulin (10) was obtained. The thin film layer was formed by applying the solution of [Formulation 10] to a 120 mesh gravure roll coater. [Formulation 10]: Thin film layer Ethyl silicate (Si(OC2H5)4: 40% by mass in terms of SiO2) ※[Si5O4(OC2H5) 12100 parts by mass of tetraethoxysilane pentamer Hydrolysis catalyst: 2% hydrochloric acid, 5 parts by mass Titanium oxide (particle diameter 10 nm) 2 parts by mass Zinc oxide (particle size 10 nm) 2 parts by mass Vinyl silane coupling agent (vinyltrimethoxysilane) 5 parts by mass Boric acid ester modified cellulose nanofiber (2% by weight aqueous solution) 100 parts by weight *3% by mass of boric acid + 78% by mass of ethyl cellosolve aqueous solution was used to make carboxymethyl cellulosolve. Cellulose nanofiber: The primary and secondary hydroxyl groups (2, 3, and 6 positions) of cellulose are converted to carboxymethylcellulose. Modified product reacted with carboxymethyl group of ethylenediamine: Fiber width 3-10 nm: Fiber length 30 ~100μm
[0047] [Example 11] The same as in Example 2, except that a thin film layer of the same sol-gel condensate as in Example 10 was added to one surface of the tarpaulin (2) in Example 2, was used. The thickness was 0.7 mm and the mass was 835 g / m. 2 The result was tarpaulin (11).
[0048] [Example 12] The same as in Example 3 except that a thin film layer of the same sol-gel condensate as in Example 10 was added to one surface of the tarpaulin (3) of Example 3, the thickness was 0.7 mm, and the mass was 835 g / m 2 The result was tarpaulin (12).
[0049] [Example 13] The same as in Example 1, except that a thin film layer (1 to 3 μm) of a sol-gel condensate containing photocatalytic titanium oxide (without surface treatment) with a primary average particle diameter of 10 nm was added to one surface of the tarpaulin (1) of Example 1, the thickness of which was 0.7 mm and the mass of which was 834 g / m 2 The tarpaulin (13) was obtained. The thin film layer was formed by applying the solution of [Formulation 11] to a 120 mesh gravure roll coater. [Formulation 11]: Thin film layer Ethyl silicate (Si(OC2H5)4: 40% by mass in terms of SiO2) ※[Si5O4(OC2H5) 12 100 parts by mass of tetraethoxysilane pentamer Hydrolysis catalyst: 2% hydrochloric acid, 5 parts by mass Photocatalytic titanium oxide sol 50 parts by mass *Nitric acid acid: Particle size 10 nm: Solid content 30% by mass in ethanol solution Vinyl silane coupling agent (vinyltrimethoxysilane) 5 parts by mass Silica sol (particle diameter 12 nm: 30% solids in ethanol solution) 50 parts by mass
[0050] [Example 14] The same as in Example 2, except that a thin film layer of the same sol-gel condensate as in Example 13 was added to one surface of the tarpaulin (2) in Example 2, was used. The thickness was 0.7 mm and the mass was 834 g / m. 2 The result was tarpaulin (14).
[0051] [Example 15] The same as in Example 3 except that a thin film layer of the same sol-gel condensate as in Example 13 was added to one surface of the tarpaulin (3) of Example 3, the thickness was 0.7 mm, and the mass was 834 g / m 2 The result was tarpaulin (15).
[0052] [Table 1]
[0053] [Table 2]
[0054] [Table 3]
[0055] [Table 4]
[0056]
Table 5
[0057] The tarpaulins (1) to (3) of Examples 1 to 3, which have at least a (surface) thermoplastic resin layer containing surface-treated titanium oxide particles (average primary particle size 1 μm), a keto / enol type tautomer, and an antifungal (algae) agent as essential components, are excellent in heat shielding properties, weather resistance, and antifungal properties, and in particular, the improved weather resistance (reduction of ultraviolet degradation) enables the service life to be extended, as revealed by comparison with the sheets obtained in Comparative Examples 1 to 3. In particular, the sheet of Comparative Example 1, which uses surface-treated titanium oxide particles (primary particle size 0.2 μm), is excellent in weather resistance but does not provide a sufficient heat shielding effect, while the sheet of Comparative Example 2, which omits the keto / enol type tautomer, is excellent in heat shielding effect but does not provide sufficient weather resistance, and the sheet of Comparative Example 3, which omits the antifungal (algae) agent, is excellent in heat shielding effect but does not provide sufficient antifungal properties. Furthermore, the tarpaulins (4) to (6) of Examples 4 to 6, in which surface-treated titanium oxide particles having an average primary particle size of 0.2 μm and surface-treated zinc oxide particles having an average primary particle size of 0.2 μm were added in a 1:1 mass ratio to the thermoplastic resin layer of the heat-shielding tent membrane structures of Examples 1 to 3, showed improved ultraviolet shielding effect (ultraviolet-A and ultraviolet-B waves) in the thermoplastic resin layer, excellent heat shielding properties and weather resistance, and in particular, improved weather resistance (reduced ultraviolet degradation) enabled further extension of the service life, as revealed by comparison with the sheets of Examples 1 to 3. Furthermore, the tarpaulins (7) to (9) of Examples 7 to 9, in which a thin film layer made of a fluorocopolymer resin containing a keto / enol tautomer and an N-OR type hindered amine in a mass ratio of 3:1 was added onto the (surface) thermoplastic resin layer of the heat-shielding tent membrane structures of Examples 1 to 3, showed improved UV shielding effect on the thermoplastic resin layer, excellent heat shielding properties and weather resistance, and in particular, improved weather resistance (reduced UV degradation) enabled further extension of the service life, as revealed by comparison with the sheets of Examples 1 to 3.Furthermore, the tarpaulins (10) to (12) of Examples 10 to 12, in which a thin film layer made of a sol-gel condensate containing surface-treated titanium oxide particles having a primary average particle size of 10 nm and surface-treated zinc oxide particles having a primary average particle size of 10 nm in a 1:1 mass ratio was added onto the (surface) thermoplastic resin layer of the heat-shielding tent membrane structures of Examples 1 to 3, showed improved ultraviolet shielding effect (ultraviolet-A and ultraviolet-B waves) for the thermoplastic resin layer, excellent heat shielding properties and weather resistance, and in particular, improved weather resistance (reduction of ultraviolet degradation) enabled further extension of the service life, as revealed by comparison with the sheets of Examples 1 to 3. Moreover, the tarpaulins (13) to (15) of Examples 13 to 15, which have a thin film layer made of a sol-gel condensate containing photocatalytic titanium oxide with a primary average particle size of 10 nm added onto the (surface) thermoplastic resin layer of the heat-shielding tent membrane structure of Examples 1 to 3, exhibit a self-cleaning effect of the thin film layer, are excellent in heat-shielding properties and weather resistance, and in particular, have improved stain resistance, which makes it possible to further extend the service life, as clarified by comparison with the sheets of Examples 1 to 3. As a result of these Examples, it was confirmed that by reducing the frequency of disposal (replacing and replacing the membrane structure) and reducing the amount of membrane material (tarpaulin) to be disposed of, and at the same time reducing the production volume of the membrane material (tarpaulin), the consumption of petrochemical resources that cause carbon dioxide emissions can be suppressed, thereby contributing to the conservation of the global environment.
[0058] [Comparative Example 1] The thermoplastic resin layer of Example 1 was prepared in the same manner as in Example 1, except that 10 parts by mass of surface-treated titanium oxide particles (average primary particle diameter: 1 μm) in [Blend 1] of Example 1 were replaced with 10 parts by mass of surface-treated titanium oxide particles (primary particle diameter: 0.2 μm) in [Blend 12]. 2 Tarpaulin (16) was obtained. By omitting the use of surface-treated titanium oxide particles with a primary average particle size of 1 μm, which have a high reflectance effect in the near-infrared region (780 to 2500 nm), the heat insulation property of tarpaulin (16) was inferior to that of tarpaulin (1). However, the weather resistance was equivalent to that of tarpaulin (1).
[0059] [Comparative Example 2] The thermoplastic resin layer was prepared in the same manner as in Example 1, except that 3 parts by mass of the benzotriazole tautomer was omitted from [Blend 1] in Example 1, and 1 part by mass of the N-OR type hindered amine was changed to 3 parts by mass [Blend 13]. 2 Tarpaulin (17) was obtained. By omitting the use of the tautomer, which is highly effective in converting and releasing ultraviolet energy into molecular vibrational energy, the weather resistance of tarpaulin (17) was inferior to that of tarpaulin (1) and it could not be used for a long time. However, its heat insulation property was the same as that of tarpaulin (1).
[0060] [Comparative Example 3] The thermoplastic resin layer of Example 1 was made the same as in Example 1 except that 0.5 parts by mass of the antifungal (algae) agent was omitted from [Mixture 1], [Mixture 14] was used. The thickness was 0.7 mm and the mass was 830 g / m 2 Tarpaulin (18) was obtained. By omitting the use of antifungal (algae) agent, the antifungal properties of tarpaulin (18) were inferior to those of tarpaulin (1) and it was not suitable for long-term use. However, its heat insulation properties were the same as those of tarpaulin (1).
[0061] [Table 6] [Industrial Applicability]
[0062] The present invention makes it possible to obtain a heat-shielding tent membrane structure with improved durability. In other words, it is possible to provide a heat-shielding tent membrane structure that can maintain a clean appearance for a long period of time due to its excellent weather resistance (reduction of ultraviolet degradation) and mold resistance (algae). Specifically, it is ideal for long-term (10 to 15 years) tent structures such as indoor sports facilities, event pavilions, traveling circuses, planetariums, and tent warehouses, and can also be used for applications lasting less than 10 years, such as architectural protection (soundproofing) sheets, pergola shades (membrane ceilings), facade sheets, lift-up sheet shutters, partition sheets, truck hoods, outdoor waterproof sheets, and house-top tents. In particular, the extension of the durability of the heat-shielding tent membrane reduces the frequency of disposal (i.e., replacement), and at the same time reduces the production volume of membrane materials, thereby reducing the consumption of petrochemical resources that cause carbon dioxide emissions, and contributing to the conservation of a sustainable global environment.
Claims
1. A waterproof sheet for a tent membrane structure, comprising a side wall periphery of a frame structure constituting a space and a canopy, the waterproof sheet being a connected sewn product of a plurality of flexible laminates each having a structure of "surface thermoplastic resin layer / fabric / backside thermoplastic resin layer", at least the surface thermoplastic resin layer containing surface-treated titanium oxide particles having a primary average particle size of 0.4 to 1.2 μm, a keto / enol type tautomer, and a fungicide as essential components, and the surface treatment applied to the surface-treated titanium oxide particles is selected from aluminum oxide, zirconium oxide, silicon oxide, and aluminum hydroxide. a thin film layer is formed on the surface thermoplastic resin layer, the thin film layer containing one or more keto / enol tautomers selected from benzotriazole tautomers, triazine tautomers, and diphenyl ketone tautomers, and an N-OR hindered amine; and
2. A waterproof sheet as described in claim 1, wherein the surface thermoplastic resin layer, or the surface thermoplastic resin layer and the back surface thermoplastic resin layer, further contain zinc oxide, or a mixture of titanium oxide and zinc oxide, and the zinc oxide and titanium oxide have a primary average particle diameter of 0.3 μm or less and a coating layer of one or more metal oxides selected from aluminum oxide, zirconium oxide and silicon oxide on the particle surface.
Citation Information
Patent Citations
Ultraviolet-resisting laminated sheet
JP1984041249A
Antifouling laminated sheet
JP2001071427A
Laminated film material high in durability and light perviousness
JP2001225423A
Aesthetic appearance keeping laminated film material
JP2003053905A
Daylighting heat insulating film material
JP2003251728A